Pengaruh Sustainable Business Innovation Dan Carbon Emission Disclosure Terhadap Nilai Perusahaan Dengan Kinerja Lingkungan Sebagai Moderasi - I GD Apri Setya Wijaya; I Gusti Ayu Purnamawati; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2025)
Abstract The research conducted on this occasion aims to determine the influence produced by sustainable business innovation and also the disclosure of carbon emissions on company value by using environmental performance as a moderator. This research was carried out on companies that carry out business activities in the manufacturing sector which are also recorded in the SRI-KEHATI Index which was successfully included in the IDX records for 2019 – 2022. This research is supported by population data of 190 companies using observations over a period of time. time 4 years. In the sampling process to make data collection easier, a purposive sampling technique was implemented, so that data was successfully obtained from 37 companies whose conditions met the criteria for sampling with a period of 4 years of observation, where the sample data used was 148 samples. The data used in this research is in the form of secondary data whose collection process was carried out online and analyzed using the SEM-PLS version 4.0 application. The results of this research were successful in finding that sustainable business innovation and disclosure of carbon emissions had a positive effect which was also accompanied by significant events on company value, environmental performance succeeded in strengthening the influence of sustainable business innovation on company value, while environmental performance did not have the ability to moderate the influence. disclosure of carbon emissions on company value. Keywords: company value, sustainable business innovation, carbon emission disclosure, environmental performance.